Charge Characteristics and Cation Exchanges Properties of Hilly Dryland Soils Aceh Besar, Indonesia - Sufardi Sufardi; Teti Arabia; Khairullah Khairullah; Karnilawati Karnilawati; Sahbudin Sahbudin; Zainabun Zainabun (Graduate Program of Syiah Kuala University, 2020)
Soil surface charge and cation exchange are important parameters of soil fertility in tropical soils. This study was conducted to investigate characteristics of surface charges and cation exchanges on four soil orders of the dryland in Aceh Besar district. The soil order includes Entisols Jantho (05o16’58.41” N; 95o37’51.82” E), Andisols Saree (05o27'15.6